2010
DOI: 10.1093/hmg/ddq023
|View full text |Cite
|
Sign up to set email alerts
|

SAHA ameliorates the SMA phenotype in two mouse models for spinal muscular atrophy

Abstract: Proximal spinal muscular atrophy (SMA) is a common autosomal recessively inherited neuromuscular disorder determined by functional impairment of alpha-motor neurons within the spinal cord. SMA is caused by functional loss of the survival motor neuron gene 1 (SMN1), whereas disease severity is mainly influenced by the number of SMN2 copies. SMN2, which produces only low levels of full-length mRNA/protein, can be modulated by small molecules and drugs, thus offering a unique possibility for SMA therapy. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 195 publications
(170 citation statements)
references
References 62 publications
9
159
2
Order By: Relevance
“…Breeding of Smn À/ À ; SMN2 tg/tg with Smn þ / À resulted in 50% SMA (Smn À/ À ; SMN2 tg/0 ) and 50% control carriers (Smn À/ þ ; SMN2 tg/0 ) in each litter. 30 We found that doses of 10 mg/kg daily and 5 mg/kg daily of JNJ-26481585 (dissolved in DMSO) were toxic leading to death before P5 and P8, respectively, irrespective of the genotype. Doses as low as 1.25 mg/kg every 5th day starting at P0 led to a mild improvement of the phenotype as seen by significantly better motor test results at P8 (Po0.001) (Figure 2b) and significantly higher weight at P8, P9 (Po0.001) and P10 (P ¼ 0.01) compared with untreated animals (Figure 2a).…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Breeding of Smn À/ À ; SMN2 tg/tg with Smn þ / À resulted in 50% SMA (Smn À/ À ; SMN2 tg/0 ) and 50% control carriers (Smn À/ þ ; SMN2 tg/0 ) in each litter. 30 We found that doses of 10 mg/kg daily and 5 mg/kg daily of JNJ-26481585 (dissolved in DMSO) were toxic leading to death before P5 and P8, respectively, irrespective of the genotype. Doses as low as 1.25 mg/kg every 5th day starting at P0 led to a mild improvement of the phenotype as seen by significantly better motor test results at P8 (Po0.001) (Figure 2b) and significantly higher weight at P8, P9 (Po0.001) and P10 (P ¼ 0.01) compared with untreated animals (Figure 2a).…”
Section: Discussionmentioning
confidence: 85%
“…SMA mice are described in detail and were bred as previously reported with 50% of the offspring being SMA mice (Smn À/ À ;SMN2 tg/0 ) and 50% control carriers (Smn À/ þ ;SMN2 tg/0 ). 30 Mice carrying homozygously the SMN2 transgene on exon 7 disrupted murine Smn background (Smn À/ À ; SMN2 tg/tg ) 40 fail to develop any motor SMA phenotype, are fertile and live for 41 year, but develop a short and thickened necrotic tail and necrotic ears. Mice heterozygous for the SMN2 transgene on exon 7 disrupted murine Smn background (Smn À/ À ;SMN2 tg/0 ) developed a severe SMA phenotype with a mean age of survival of B10 days.…”
Section: Micementioning
confidence: 99%
See 2 more Smart Citations
“…HDAC-inhs have been tested in vitro and in vivo: hydroxybutyric acid was the first compound shown to increase SMN2 levels in lymphoblastoid cell lines from SMA patients and to also increase the lifespan of a SMA mice [Chang et al, 2001]. Since then, valproic acid, phenylbutyrate, trycostatin A, and SAHA have also been shown to increase SMN levels in vitro and/or to improve the survival of SMA models in pre-clinical studies [Brichta et al, 2003;Sumner et al, 2003;Andreassi et al, 2004;Hahnen et al, 2006;Avila et al, 2007;Narvel et al, 2008;Riessland et al, 2010]. Valproic acid and phenylbutyrate have been tested in patients with SMA but with discordant outcomes.…”
Section: Sma Treatment: How When and Where?mentioning
confidence: 99%